A Pseudocapacitor Diode Based on Ion‐Selective Surface Redox Effect. Issue 10 (10th January 2023) - Tang, Pei; Tan, Wuyang; Li, Fangzhou; Xue, Shan; Ma, Yihui; Jing, Pengwei; Liu, Yanghui; Zhu, Jian; Yan, Xingbin
Abstract: Supercapacitor diode (CAPode) is a novel device that integrates ion diode functionality into a conventional electrical double‐layer capacitor and is expected to have great applications in emerging fields such as signal propagation, microcircuit rectification, logic operations, and neuromorphology. Here, a brand new pseudocapacitor diode is reported that has both high charge storage (50.2 C g −1 at 20 mV s −1 ) and high rectification (the rectification ratio of 0.79 at 200 mV s −1 ) properties, which is realized by the ion‐selective surface redox reaction of spinel ZnCo2 O4 in aqueous alkaline electrolyte. Furthermore, an application of the integrated device is demonstrated in the logic gate of circuit system to realize the logic operations of "AND" and "OR". This work not only expands the types of CAPodes, but also provides a train of thought for constructing high‐performance capacitive ionic diodes. Abstract : A pseudocapacitor diode is proposed for the first time, which is constructed by the ion‐selective surface redox mechanism of spinel ZnCo2 O4 in aqueous electrolyte KOH, thus successfully integrating the function of blocking the unidirectional current response of a diode into an aqueous pseudocapacitor with fast ion conduction capability.